If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 12 = -21 Reorder the terms: 12 + b = -21 Solving 12 + b = -21 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + b = -21 + -12 Combine like terms: 12 + -12 = 0 0 + b = -21 + -12 b = -21 + -12 Combine like terms: -21 + -12 = -33 b = -33 Simplifying b = -33
| 1-2c-3c+100= | | 9y-8+4y= | | 3x/x^2 | | 9/540 | | ln(3x^2)-2x=0 | | 26+48x=-502 | | X=6-21 | | 10=n/6+9 | | -3(2t-2)+4t=7t-8 | | 6/174 | | 2/194 | | -0.5=-2x+8.1 | | 8/668 | | 18-33x=180 | | -3y-2y-y= | | 3/237 | | 3/261 | | 4a+5-a+2= | | 8z-z=-2+2z-1-2 | | 7/336 | | 9/603 | | 9t+5t-3t= | | 6/504 | | 28-4d=59-17 | | 7/322 | | 7/413 | | 7t+8(9t-1)=8(3t+9) | | 23-44x=199 | | 4/264 | | -9(x+1)+5(3x-5)=5(x-4)+13 | | 2z+15+3x-5= | | 3/195 |